Predispositions, partisan media, and political beliefs about female presidency in South Korea and the United States - Yonghwan Kim; Seckjun Jang (Humanities & Social Sciences Communications)
Abstract This study investigated the effects of political predispositions and partisan media use on beliefs about candidates’ gender in political campaigns. The analysis of two national surveys, one in South Korea (Study 1) and one in the United States (Study 2), found associations between individuals’ political predispositions and beliefs regarding candidates’ gender that aligned with their political ideology and party affiliation. The results also showed that partisan media use was significantly related to such beliefs. In addition, the findings demonstrated a mechanism through which partisan media use significantly influenced individuals’ voting intention via beliefs. In other words, frequent exposure to politically slanted media increased the activation of negative or positive beliefs, which in turn affected citizens’ voting intention.